Physical and Chemical Properties and Quality Control Methods of Hyaluronic Acid (Review) - A. Kh. Amandusova; K. R. Saveleva; A. V. Morozov; V. A. Shelekhova; L. V. Persanova; S. V. Polyakov; V. N. Shestakov (Разработка и регистрация лекарственных средств, 2020)
Introduction. This review describes the physicochemical properties that determine the use of hyaluronic acid in ophthalmology. We have studied methods for determining hyaluronic acid using various analytical methods.Text. Hyaluronic acid is a high molecular weight glycosaminoglycan that consists of repeating disaccharides of N-acetylglucosamine and D-glucuronic acid. Carboxyl, hydroxyl and acetoamide groups give hydrophilic properties to the molecule of this anionic heteropolysaccharide. Depending on how the hyaluronic acid is obtained, its molecular weight varies over a wide range. Researchers developed methods for controlling hyaluronic acid, which include the turbidimetric titration method, the method of high-performance capillary electrophoresis and high-performance liquid chromatography and IR spectroscopic method.Conclusion. Due to its properties, hyaluronic acid is widely used as an active ingredient in pharmaceutical preparations. Today, there are a number of methods for the determination of hyaluronic acid, including the method of turbidimetric titration, the method of capillary electrophoresis. High performance liquid chromatography (HPLC) and IR spectroscopy methods are presented in the Japanese Pharmacopoeia and the European Pharmacopoeia. These techniques are widely used due to their high reproducibility, accuracy, and relative simplicity.